2014
DOI: 10.1016/j.colsurfb.2014.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iron oxide loading on magnetoferritin structure in solution as revealed by SAXS and SANS

Abstract: Synthetic biological macromolecule of magnetoferritin containing an iron oxide core inside a protein shell (apoferritin) is prepared with different content of iron. Its structure in aqueous solution is analyzed by small-angle synchrotron X-ray (SAXS) and neutron (SANS) scattering.The loading factor (LF) defined as the average number of iron atoms per protein is varied up to LF=800. With an increase of the LF, the scattering curves exhibit a relative increase in the total scattered intensity, a partial smearing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The maximum particle dimension (D max )f rom the pair-distance distribution function (p(r)) was calculated to be 23 nm ( Figure 2B). Thed istribution pattern of p(r)w ith ah igh-r shifted peak was similar to that of ah ollow capsule particle such as the iron-storage protein apoferritin, [13] suggesting that the nanoparticle has ahollow inner space.Inaddition, alowresolution model composed of small beads (dummy atoms) was constructed from the SAXS data using the ab initio modeling program DAMMIF, [14] and the results indicated that the protein complex shape resembles as pherical hollow particle ( Figure 2B). Thed ummy-atom model and the manually designed rigid-body model of the nanoparticle superimposed well ( Figure S5 and S9), and I(q)s imulated from the rigid-body model roughly resembles I(q)o btained from the SAXS experiment (c 2 = 1.825) ( Figure S10).…”
mentioning
confidence: 67%
“…The maximum particle dimension (D max )f rom the pair-distance distribution function (p(r)) was calculated to be 23 nm ( Figure 2B). Thed istribution pattern of p(r)w ith ah igh-r shifted peak was similar to that of ah ollow capsule particle such as the iron-storage protein apoferritin, [13] suggesting that the nanoparticle has ahollow inner space.Inaddition, alowresolution model composed of small beads (dummy atoms) was constructed from the SAXS data using the ab initio modeling program DAMMIF, [14] and the results indicated that the protein complex shape resembles as pherical hollow particle ( Figure 2B). Thed ummy-atom model and the manually designed rigid-body model of the nanoparticle superimposed well ( Figure S5 and S9), and I(q)s imulated from the rigid-body model roughly resembles I(q)o btained from the SAXS experiment (c 2 = 1.825) ( Figure S10).…”
mentioning
confidence: 67%
“…The structural features of several kinds of aqueous magnetic fluids [143][144][145][146], as well as surfactant/polymer solutions [147][148][149], which are used for magnetic nanoparticle stabilization in water, were investigated in detail by SANS (Figures 12 and 13). Additionally, magnetic nanoparticles with bio-macromolecules were successfully studied by SANS and SAXS [150,151] (Figure 14). Thus, investigations of magnetic fluid stability at various amounts of surfactants and aggregation of MNPs were undertaken by SAS for ferrofluids based on non-polar and polar (aqueous) carriers.…”
Section: Neutron and X-ray Scatteringmentioning
confidence: 99%
“…The maximum particle dimension ( D max ) from the pair‐distance distribution function ( p ( r )) was calculated to be 23 nm (Figure B). The distribution pattern of p ( r ) with a high‐ r shifted peak was similar to that of a hollow capsule particle such as the iron‐storage protein apoferritin, suggesting that the nanoparticle has a hollow inner space. In addition, a low‐resolution model composed of small beads (dummy atoms) was constructed from the SAXS data using the ab initio modeling program DAMMIF , and the results indicated that the protein complex shape resembles a spherical hollow particle (Figure B).…”
Section: Figurementioning
confidence: 75%